2019
DOI: 10.1177/1203475419856611
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen Application, Safety, and Sun Protection: The Evidence

Abstract: Recently in Canada, there has been an effort to create consistent messaging about sun safety as there is a lack of up-to-date evidence-based guidelines regarding sun-protection measures. This review aimed to provide updated, evidence-based recommendations on sunscreen application, safety, and sun protection regarding the following topics for which there is clinical uncertainty: physical barriers, sunscreen properties, sunscreen application, and risk-benefit analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 75 publications
(122 reference statements)
2
61
0
7
Order By: Relevance
“…An SPF of >30 was used by most students (59%) in our study. is is in agreement with the current recommendations of using sunscreen with an SPF of at least 30 [14]. Standard testing of SPF in sunscreens is done using a thickness of 2 mg/cm 2 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…An SPF of >30 was used by most students (59%) in our study. is is in agreement with the current recommendations of using sunscreen with an SPF of at least 30 [14]. Standard testing of SPF in sunscreens is done using a thickness of 2 mg/cm 2 .…”
Section: Discussionsupporting
confidence: 87%
“…In fact, several recent studies demonstrated that higher SPF sunscreens provided more protection [16][17][18]. Water-resistant sunscreen with a water-in-oil formulation (such as thick creams) provides better protection [14]. Although only some students used water-resistant sunscreen, a cream formulation was the most common in our study.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations